Intolerance against the Right to Freedom of Religion and Belief in the Termination of the Piodalan Ritual in Bantul Regency - Jeremias Palito; Tiara Almira Raila; Tasya Nafiisah (IHSA Institute, 2020)
Every human being in the world has Human Rights. One of them is the right to freedom of religion and belief. This right has been included in the International Covenant on Political and Civil Right, and in the 1945 Constitution, considering that Indonesia is a religious state. Indonesian people are allowed to embrace their respective religions. However, in 2019, cases of intolerance towards certain religious groups still occurred. The Piodalan ritual that was followed by Hindus and Buddhists in Bantul Regency was dismissed by local residents because it was considered worrying. The ritual had to be carried out at the house of one of the residents, because the Hindu houses of worship in Bantul Regency were still very minimal. In this article, we will discuss the provisions for the establishment of places of worship in Indonesia as well as the conceptions of human rights arrangements in Indonesia and in the context of international law. Method used in this paper is library research. This research shows that Bantul Regency lacks house of worship and there have been several intolerance cases happened in the past. In Indonesia, the enforcement of the right to freedom of religion and belief is still weak, even though there are already several legal instruments, including the 1945 Constitution, the Human Rights Law, and even international instruments, such as the UDHR and ICCPR which has been ratified by Indonesia.